Review: Ecological impact and bioactive profile of the invasive species Solanum elaeagnifolium in the Gaza Strip, Palestine (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Abou Auda M, Eleyan M. 2025. Review: Ecological impact and bioactive profile of the invasive species Solanum elaeagnifolium in the Gaza Strip, Palestine. Biodiversitas 26: 3485-3513. Solanum elaeagnifolium (Silverleaf nightshade) is an aggressive invasive species in the Middle East, particularly in the Gaza Strip, Palestine, where it poses significant ecological and agricultural threats. This review provides a comprehensive analysis of the botany, ecology, phytochemistry, pharmacology, and toxicology of S. elaeagnifolium in the Gaza Strip. It is the first study to focus on its invasive potential and bioactivity in this region, with an emphasis on the need for monitoring and effective control strategies. A comprehensive literature review was conducted, sourcing data from PubMed, Scopus, Web of Science, and Google Scholar databases up to April 2025. The plant contains flavonoids, glycoalkaloids, phenolic acids, and saponins. Nutritional content includes crude fiber (28-32% in leaves; 27-32% in flowers), protein (13-14%), potassium (2.6% in leaves; 3.3% in flowers), and phosphorus (0.21-0.24%). Toxicological studies reported hepatotoxic effects at 2000 mg/kg fruit extract (p
Keywords: Invasive species, phytochemistry, silverleaf nightshade, Solanum elaeagnifolium, weed